Effects of Different Fermentation and Clarification Methods on the Color, Physicochemical Characteristics, and Aroma Profile of Healthcare Cornus–Kiwifruit Composite Wine - Cuiyan Zeng; Xueru Zhang; Junxia Zhang; Shuiyan Pan; Keqin Chen; Yulin Fang (Foods)
A lack of distinctive features has become a significant factor limiting the development of kiwi wine. However, the rapidly growing trend of healthcare-oriented composite fruit wine with health functions and diverse flavors presents a way to address this issue. A kiwi wine fermentation method was investigated by incorporating the medicinal and edible fruits of Cornus officinalis. The results indicate that adding Cornus officinalis introduced a unique component known as iridoid glycosides to the wine. Additionally, the concentrations of phenols, total iridoid glycosides, and most aroma compounds in the wine increased after the addition of crushed Cornus officinalis following alcoholic fermentation. As the proportion of Cornus officinalis in the kiwi wine rose, so did polyphenolic substances and total iridoid glycosides; however, this diminished the wine’s clarity. Additionally, a yeast addition of 200 mg/L demonstrated optimal fermentation capabilities, and a bentonite addition of 1.1 g/L exhibited an outstanding clarifying effect. These results not only enhance nutritional value and quality but also provide a theoretical foundation for the production of high-quality Cornus–kiwifruit composite wine.